Hygienic assessment of working conditions of the sinter operator of the metallurgical enterprise - Sharavara, L. P.; Chebanenko, A. О.; Шаравара, Лариса Павлівна (My University, 2021)
Introduction. The metallurgical industry is one of the developed industries in Ukraine, whose enterprises are located mainly in four regions of the country: Donetsk, Zaporizhia, Luhansk and Dnipropetrovsk [1]. At the workplaces of metallurgical workers there are harmful production factors of various nature, which can lead to occupational and work-related pathology [2, 3]. Therefore, the study of working conditions in the workplace of metallurgical workers remains a topical issue and needs attention. The aim of the study: hygienic assessment of the working conditions of the sinter operator of the metallurgical enterprises. Materials and methods. A study of working conditions at 44 workplaces of sinter operators of a metallurgical enterprise for 2011-2020 years. The study of factors of the working microclimate was carried out using the device ECOTENSOR-MK (Ukraine), the number of studies of working microclimate - 180 measurements, the level of infrared radiation - 30 measurements), air pollution of the working area of workers was carried out using a gas analyzer PALLADIUM-3M-01 − 1005 research, the study of working noise and vibration was conducted using a noise and vibration analyzer S-LIGHT and OCTAVE 110A - 50 studies.